2015
DOI: 10.1371/journal.pone.0133320
|View full text |Cite
|
Sign up to set email alerts
|

First-Pass Meconium Samples from Healthy Term Vaginally-Delivered Neonates: An Analysis of the Microbiota

Abstract: BackgroundConsiderable effort has been made to categorise the bacterial composition of the human gut and correlate findings with gastrointestinal disease. The infant gut has long been considered sterile at birth followed by rapid colonisation; however, this view has recently been challenged. We examined first-pass meconium from healthy term infants to confirm or refute sterility.MethodsHealthy mothers were approached following vaginal delivery. First-pass meconium stools within 24 hours of delivery were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
4
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 24 publications
7
112
4
4
Order By: Relevance
“…Contrary to the traditional belief that the human neonatal respiratory tract is sterile at birth, current studies indicate that the human respiratory tract microbial colonization begins in utero 100,101 or shortly after birth 102,103 . A recent study demonstrated that the lung microbiome, including the relative abundance of bacterial phyla and diversity index of the preterm and term neonates were similar at birth irrespective of the gestational age and the mode of delivery.…”
Section: Pathogenesiscontrasting
confidence: 91%
“…Contrary to the traditional belief that the human neonatal respiratory tract is sterile at birth, current studies indicate that the human respiratory tract microbial colonization begins in utero 100,101 or shortly after birth 102,103 . A recent study demonstrated that the lung microbiome, including the relative abundance of bacterial phyla and diversity index of the preterm and term neonates were similar at birth irrespective of the gestational age and the mode of delivery.…”
Section: Pathogenesiscontrasting
confidence: 91%
“…In our quantitative investigation of the gut microbiota composition in Japanese infants, we detected several bacterial clades, albeit with varying detection rates and numbers, in the firstpass meconium of 95% infants [17], which suggests that several bacterial communities inhabit the intrauterine environment and may provide the pioneer inoculum for gut microbiota colonization. Notably, previous studies on fullterm babies reported the detection of bacteria in about 65-75% of total babies studied [18,19]. This difference may be ascribed to differences in the detection sensitivity of the methods used and hence support the advantage of the high sensitivity of our real-time quantitative (RT-qPCR)-based approach.…”
Section: Early-life Gut Microbiota In Relation To the Mode Of Deliverymentioning
confidence: 52%
“…We detected bacteria in the meconium of 95% babies while rest 5% samples appeared to be sterile (i.e., no bacteria detected). However, previous studies on term infants reported the presence of bacteria in 66% (using 16S rRNA gene-targeted FISH method) (Hansen et al, 2015) and 77% (using 16S/23S rRNA gene-targeted qPCR) (Martin et al, 2016) of total babies studied. This difference can most possibly be ascribed to differences in the detection sensitivities of the methods used, and hence could corroborate the advantage of high sensitivity of our RT-qPCR assays.…”
Section: Discussionmentioning
confidence: 90%
“…However, some recent studies have elegantly reported the presence of bacteria in placenta (Aagaard et al, 2014; Collado et al, 2016), amniotic fluid (Oh et al, 2010; Collado et al, 2016), and umbilical cord blood (Jimenez et al, 2005), thereby manifesting that the fetus is already exposed to a variety of bacteria in utero . Several studies have also detected various bacteria in the meconium of healthy babies (Gosalbes et al, 2013; Hu et al, 2013; Del Chierico et al, 2015; Hansen et al, 2015; Collado et al, 2016), further evidencing that the gut microbial colonization may already begin before birth. However, quantitative data on the types and particularly the population levels (i.e., the absolute count) of bacteria that may be present in the meconium is still sparse.…”
Section: Introductionmentioning
confidence: 96%